Prevalence of professional burnout syndrome among dentists in the education and health sectors in the city of Guadalajara, Mexico, 2012 - Castañeda-Aguilera, Enrique; García-de Alba, Javier E. (Revista Facultad de Odontología Universidad de Antioquia, 2013)
Introduction: the goal of this study was to determine the prevalence of professional burnout syndrome among dentists working in the education and health sectors and to analyze socio-demographic and labor-related risk factors. Methods: this was an observational, descriptive, transversal study through a census with dental personnel in the metropolitan area of Guadalajara, Mexico, the Social Security Institute of Mexico, and the University of Guadalajara; the sample included 138 professionals who completed an identification form and the self-administered Maslach Burnout Inventory-Human Services Survey. Descriptive statistics and inferential analyzes were conducted with SPSS 15.0 and Epi-info V6.1. Results: 92% of participants responded the survey, and professional burnout syndrome was found in 52% of them. Significant differences were observed in relation to tenured jobs. Conclusions: professional burnout syndrome is frequent among dentists (52%). The main risk factors associated to it include: working in a health institution, being a male, being over 40 years, with no permanent partner and with more than 15 years with a partner, not having children, being a specialist, with 10 or more years of seniority and in the current job, day shift, and having tenure while working somewhere else. Emotional exhaustion also makes part of the syndrome. The average levels of the subscales are generally near normal. A negative correlation was found between emotional exhaustion subscales and depersonalization, and a positive relation between the lack of personal accomplishment at work and presence of the syndrome.